2016
DOI: 10.1007/s00330-016-4424-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration versus core needle biopsy for diagnosis of thyroid malignancy and neoplasm: a matched cohort study

Abstract: • Diagnostic performances of FNA and CNB for thyroid malignancy and neoplasm were compared. • FNA showed comparable performances to CNB both before and after statistical matching. • There may be no benefit in performing CNB, given the comparable performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Two main advantages of CNB have been previously suggested: a high diagnostic accuracy for thyroid malignancy; and a low false-positive rate for follicular neoplasm. Regarding the diagnostic accuracy for thyroid malignancy, several studies compared the results of CNB and FNA (4,11,(20)(21)(22)(23). In these studies, both CNB (98-100%) and FNA (95-100%) showed high specificities; however, the sensitivities were slightly higher for CNB than for FNA (81-96% vs. 61-84%).…”
Section: Discussionmentioning
confidence: 99%
“…Two main advantages of CNB have been previously suggested: a high diagnostic accuracy for thyroid malignancy; and a low false-positive rate for follicular neoplasm. Regarding the diagnostic accuracy for thyroid malignancy, several studies compared the results of CNB and FNA (4,11,(20)(21)(22)(23). In these studies, both CNB (98-100%) and FNA (95-100%) showed high specificities; however, the sensitivities were slightly higher for CNB than for FNA (81-96% vs. 61-84%).…”
Section: Discussionmentioning
confidence: 99%
“…Seven of these hospitals also published data about CNB and reported its advantages over FNA; these hospitals were categorized as favoring CNB. One hospital focused on the weaknesses or disadvantages of CNB in four papers [22,43,58,59]; despite publishing papers on CNB, we categorized this hospital as not favoring CNB. Head and neck surgeons working at five other hospitals without a paper on CNB were contacted to obtain information on their use of CNB, and they confirmed that they rarely used CNB in clinical settings.…”
Section: Differences In the Proportions Of Diagnoses On Consecutive Fmentioning
confidence: 99%
“…Ultrasonography (US) guided-fine-needle aspiration (FNA) has been used as the primary diagnostic tool for thyroid nodules, owing to its safety, simplicity, cost-effectiveness, and reliability. 1 Since early 2010, several articles have demonstrated the safety and tolerability of core-needle biopsy (CNB) for the evaluation of thyroid nodules, as well as its diagnostic efficacy. [2][3][4][5][6][7][8] Unlike FNA, which has been validated as a standard diagnostic method for over half a century, the value of CNB has not yet been fully evaluated for diagnosing thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%
“…12 To overcome this weakness, some investigators have suggested CNB as alternative or complementary diagnostic tool for thyroid nodules, 5,8,[13][14][15][16] even though CNB does not show superior diagnostic performance to FNA for diagnosing thyroid cancer and poses a higher rate of post-biopsy hematoma than FNA. 1,17 Many favorable results for CNB have been found in studies conducted by experienced radiologists and CNB has even been used to diagnose small nodules, 5,8,15,16,18 even micronodules not indicated for FNA in prestigious guide-…”
Section: Introductionmentioning
confidence: 99%